Evaluation of sintered gears in operational conditions - Rosiak, Mariusz; Napiórkowski, Jerzy; Lemecha, Magdalena (MATEC web of conferences, 2017)
This article presents the description of tested gears that were made from sintered material, as well as of gears made of grade 16MnCr5 steel (number 1.7131), which are installed in transmissions of power tools. The procedure for the gear tests was described, and a test bench and the methodology for carrying out the tests were presented. The aim of the article was to examine whether sintered gears could replace gears made of steel 16MnCr5 while maintaining the required stability in operating conditions. The results of the evaluation of geometry changes and the results of metallographic examinations were presented. The results achieved were analyzed and the sintered gear technology was evaluated. Recommendations were formulated concerning the enhancement of the technology with which sintered gears are produced in order to obtain products with even higher operational properties.